In2O3-Ti3C2@GOx biological heterojunction, hydrogel microneedle and preparation method and application thereof

By designing load In2O3-TI3C2@GOX Water Gel micro-needle with heterogeneity, using the production of living and living oxygen under the condition of optical power, solving the problem of poor killing effect on diabetic infectious wound disease in the existing technology , Achieve effective killing and healing of the wound.

CN118987210BActive Publication Date: 2025-01-28南昌大学第一附属医院
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411487266.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing hydrogel micro-killing effect of pathogenic bacteria on infectious wounds of diabetes is average, resulting in poor treatment effect.

Method used

Design a hydrogel microchaser with hydrogels that loads in IN2O3-TI3C2@GOX biological heterogeneous knot. Bio-heterogeneous knots are formed through IN2O3 and Ti3C2, loaded glucose oxidase, and uses life-life oxygen under optical power to enhance the killing ability of bacteria to kill bacteria. Essence

Benefits of technology

The effective pathogenic bacteria of the infectious wounds of diabetes and promoting wound healing have provided a potential treatment strategy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118987210B_ABST
    Figure CN118987210B_ABST
Patent Text Reader

Abstract

The invention discloses an In2O3-Ti3C2@GOx biological heterojunction, a hydrogel microneedle, a preparation method and an application thereof, and relates to the technical field of hydrogel microneedles. The preparation method of the In2O3-Ti3C2@GOx biological heterojunction comprises: adding In(NO3)3·xH2O (x is 1-10) and Ti3C2 to a solvent, mixing, heating, and centrifuging to obtain a precipitate; washing and drying the precipitate, calcining under oxygen-isolating conditions to obtain In2O3-Ti3C2; soaking the In2O3-Ti3C2 in a glucose oxidase solution, freeze-drying, and obtaining a hydrogel microneedle loaded with the In2O3-Ti3C2@GOx biological heterojunction, a preparation method and an application thereof. Compared with the prior art, the hydrogel microneedle of the invention can generate active oxygen and redox glutathione in the presence of hydrogen peroxide, enhance the killing effect of active oxygen on bacteria, and improve the therapeutic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogel microneedles, and in particular to an In2O3-Ti3C2@GOx bioheterojunction, a hydrogel microneedle, and a preparation method and application thereof. Background Art

[0002] As a common disease, diabetic wound infection seriously affects the quality of life of patients. The treatment cycle is long, and improper control can lead to limb infection and necrosis, often requiring amputation to avoid the serious consequences of septic shock or even death. Diabetic infected wounds are difficult to heal because high blood sugar damages peripheral blood vessels and nerves, resulting in a lack of blood supply and electrophysiological signals in the wound. At the same time, high blood sugar damages immune function, making the wound susceptible to infection. The massive proliferation of pathogens affects tissue regeneration and destroys the original tissue. How to treat diabetic infected wounds is currently a difficult problem in clinical treatment.

[0003] Bioheterojunction is a new type of material, derived from the heterojunction in the field of semiconductor and photocatalysis. It is an interface region formed by the contact interface of two different semiconductors. It has a higher electron-hole separation efficiency and promotes the generation of active oxygen (·OH, 1 O2) to play a biological function, and different semiconductor compositions can give it other properties and functions. In2O3 is an n-type semiconductor commonly used in battery coatings, with a band gap of 2.8 eV, high photocatalytic activity, and peroxidase activity, but its band gap is too wide, which reduces the utilization of light. Introducing narrow band gap semiconductors to change its band gap structure will enhance its catalytic activity. Ti3C2 is a semiconductor material with a two-dimensional planar structure, which has the characteristics of huge specific surface area, high photothermal conversion efficiency, excellent antibacterial properties, and a narrow band gap (1.4 eV).

[0004] Glucose oxidase (GOx) can catalyze glucose to produce gluconic acid and hydrogen peroxide, which can effectively reduce the glucose concentration in the tissue environment, restore tissue vitality, and reduce high sugar damage. Efficient use of glucose oxidase is a hot issue in medical dressings for diabetic wounds.

[0005] Hydrogel microneedles are made of natural polymer materials and synthetic polymer materials through chemical cross-linking and micro-molding. They have the characteristics of water absorption and expansion, loose porous structure, array-type needle tip structure, and efficient drug loading. They can effectively penetrate the skin, tissue mucosa, etc., expand after absorbing tissue fluid, and then continuously release drugs to exert a therapeutic effect.

[0006] However, the hydrogel microneedles in the prior art have a general killing effect on pathogens of diabetic wounds, resulting in a general treatment effect. Therefore, it is urgent to design a hydrogel microneedle with a better killing effect on pathogens of diabetic infectious wounds. Summary of the invention

[0007] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide an In2O3-Ti3C2@GOx bioheterojunction, a hydrogel microneedle loaded with In2O3-Ti3C2@GOx bioheterojunction, and a preparation method and application thereof.

[0008] The technical solution of the present invention is as follows:

[0009] In a first aspect, the present invention provides a method for preparing an In2O3-Ti3C2@GOx bioheterojunction, comprising the following steps:

[0010] S1. Add In(NO3)3·xH2O and Ti3C2 to a solvent and mix well to obtain a mixed solution; heat the mixed solution, and centrifuge to obtain a precipitate after the reaction is completed; wash and dry the precipitate, and then calcine it under oxygen-free conditions to obtain In2O3-Ti3C2; wherein x in In(NO3)3·xH2O is 1 to 10;

[0011] S2. Soaking the In2O3-Ti3C2 in a glucose oxidase solution and freeze-drying the solution to obtain an In2O3-Ti3C2@GOx bioheterojunction.

[0012] Optionally, the preparation method of Ti3C2 comprises the following steps:

[0013] Add hydrofluoric acid, concentrated hydrochloric acid and deionized water to a reaction container and mix well; heat the reaction container, and when the heating temperature rises to 30°C to 40°C, add titanium aluminum carbide to the reaction container, continue stirring for 8 h to 16 h, centrifuge to obtain a black precipitate, and wash until the pH is neutral;

[0014] Adding LiCl into deionized water and dissolving it to obtain a LiCl solution;

[0015] The LiCl solution and the black precipitate are mixed and stirred for 8 h to 16 h, the obtained solution is centrifuged to remove the supernatant, deionized water is added and centrifuged again, the obtained black liquid is subjected to ultrasonic treatment, and finally dried to obtain a single layer of Ti3C2;

[0016] The ratio of the added amount of hydrofluoric acid, concentrated hydrochloric acid, titanium aluminum carbide and LiCl is 8 mL~12 mL: 8 mL~12 mL: 0.8 g~1.2 g: 0.8 g~1.2 g;

[0017] The concentration of the hydrofluoric acid is 45wt%~55wt%;

[0018] The concentration of the hydrochloric acid is 10 mol / L~14 mol / L.

[0019] Optionally, in step S1,

[0020] The heating temperature is 100℃~140℃, and the heating time is 20 h~28 h;

[0021] The drying temperature is 50℃~70℃, and the drying time is 8 h~12 h;

[0022] The calcination temperature is 480℃~520℃, and the calcination time is 1.5h~2.5h;

[0023] The solvent includes anhydrous ethanol and aqueous ammonia with a concentration of 20wt% to 30wt%;

[0024] The ratio of the added amounts of In(NO3)3·xH2O, Ti3C2, anhydrous ethanol and ammonia water is 80mg~120mg:80mg~120mg:25mL~35mL:6mL~8mL; wherein x is 1~10;

[0025] Optionally, in step S2,

[0026] The concentration of the glucose oxidase solution is 1.5 mg / mL to 2.5 mg / mL;

[0027] The ratio of the added amount of In2O3-Ti3C2 to the glucose oxidase solution is 8 mg~12 mg: 80 μL~120 μL;

[0028] The soaking temperature is -5℃~-3℃, and the soaking time is 10h~14h.

[0029] In a second aspect, the present invention provides an In2O3-Ti3C2@GOx bioheterojunction prepared by the above method.

[0030] In a third aspect, the present invention provides a hydrogel microneedle loaded with In2O3-Ti3C2@GOx bioheterojunction, wherein the preparation raw materials thereof include: methacrylic anhydride-treated gelatin, In2O3-Ti3C2@GOx bioheterojunction and a photoinitiator.

[0031] In a fourth aspect, the present invention provides a method for preparing a hydrogel microneedle loaded with an In2O3-Ti3C2@GOx bioheterojunction, comprising the following steps:

[0032] Mixing methacrylic anhydride gelatin with deionized water and heating to obtain a 15 wt % to 25 wt % methacrylic anhydride gelatin aqueous solution;

[0033] The base solution is prepared from a 15-25wt% methacrylic anhydride gelatin aqueous solution and a photoinitiator, wherein the amount of the photoinitiator added is 2wt‰~5wt‰ of the In2O3-Ti3C2@GOx methacrylic anhydride gelatin sample dispersion;

[0034] The preparation method of the In2O3-Ti3C2@GOx gel suspension specifically includes:

[0035] The methacrylic anhydride gelatin aqueous solution is mixed with the In2O3-Ti3C2@GOx bioheterojunction to obtain an In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion;

[0036] The In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion is evenly mixed with a photoinitiator to obtain an In2O3-Ti3C2@GOx gel suspension;

[0037] The In2O3-Ti3C2@GOx gel suspension is poured into the microneedle mold, dried, and bubbles are removed to fill the needle tip with the In2O3-Ti3C2@GOx gel suspension. After adding the substrate solution, the mold is exposed to light and demolded to obtain the In2O3-Ti3C2@GOx composite microneedle.

[0038] Optionally, the method for preparing the methacrylic anhydride gelatin comprises:

[0039] Add gelatin to deionized water, heat to 45°C-50°C and stir to fully dissolve it, then add methacrylic anhydride solution to the solution, continue stirring, put the solution into a dialysis bag after stirring, dialyze with distilled water for 68 h-76 h, then centrifuge to remove the precipitate, and evenly freeze-dry the centrifuged methacrylated gelatin solution to obtain methacrylated gelatin;

[0040] Wherein, the mass ratio of the gelatin, methacrylic anhydride solution and deionized water is 1-3:0.5-1.5:16-20.

[0041] Optionally, the concentration of the In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion is 2 mg / mL to 5 mg / mL;

[0042] The In2O3-Ti3C2@GOx methacryloyl gelatin sample dispersion and the photoinitiator are added into a container, and stirred evenly at 35°C~39°C to obtain the In2O3-Ti3C2@GOx gel suspension, wherein the amount of the photoinitiator added is 2wt‰~5wt‰ of the amount of the In2O3-Ti3C2@GOx methacryloyl gelatin sample dispersion added.

[0043] In a fifth aspect, the present invention provides an application of the above-mentioned hydrogel microneedle or the hydrogel microneedle prepared by the above-mentioned method in the preparation of a product for treating diabetic wounds.

[0044] The present invention has at least one of the following beneficial effects:

[0045] 1. The present invention forms a biological heterojunction by connecting In2O3 and Ti3C2. Ti3C2 and In2O3 form a heterojunction at the interface and produce a staggered lattice, which can exert antibacterial and catalytic properties; and successfully loads glucose oxidase on In2O3-Ti3C2, which can convert glucose in the tissue environment into H2O2. In2O3-Ti3C2@GOx can generate reactive oxygen in the presence of hydrogen peroxide, and can oxidize reduced glutathione (GSSH), thereby enhancing the killing effect of reactive oxygen on bacteria and achieving effective killing of pathogens on the wound surface.

[0046] 2. The In2O3-Ti3C2@GOx bioheterojunction hydrogel microneedle (GITG) provided by the present invention is synthesized using natural polymer gelatin, which avoids the toxic side effects and allergic reactions caused by other polymer microneedles. At the same time, the introduction of methacrylic anhydride side chains increases its mechanical strength, so that it has the mechanical strength to penetrate the dermis of the skin, and can achieve non-invasive transdermal administration. In the diabetic infectious rat model, for refractory infections and deep infections, the glucose oxidase possessed by the In2O3-Ti3C2@GOx bioheterojunction of the present invention can effectively utilize glucose in the tissue environment to convert it into H2O2, and at the same time, it can produce a low-temperature thermal treatment effect under 808 nm near-infrared light irradiation for deep antibacterial. In addition, under light drive, the heterojunction structure can be used to excite electron transitions to generate electron-hole pairs, thereby generating ·OH, 1 O2 active oxygen effectively kills pathogens on the wound surface. After eliminating the infection, GITG microneedles promote the proliferation and regeneration of the skin, with good application effects, providing a potential treatment strategy for diabetic infected wounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1The physicochemical characterization of the In2O3-Ti3C2@GOx bioheterojunction prepared by the present invention. Among them, a is the scanning electron microscope image of Ti3AlC2, Ti3C2, In2O3, In2O3-Ti3C2 (INT), and In2O3-Ti3C2@GOx (INTG); b is the X-ray diffraction (XRD) experimental results of Ti3AlC2, Ti3C2, In2O3, and In2O3-Ti3C2@GOx (INTG); c is the X-ray photoelectron spectroscopy (XPS) experimental results of Ti3C2, In2O3, and INTG; d is the semi-quantitative result of scanning electron microscope energy spectrum analysis (EDS); f is the scanning electron microscope energy spectrum analysis (EDS) diagram; e is the Fourier transform infrared spectroscopy results of GOx, ING, and INTG.

[0048] Figure 2 The heterojunction structure characterization of the In2O3-Ti3C2@GOx biological heterojunction prepared by the present invention. Among them, a is a transmission electron microscope photo of INTG; b is the UV-visible diffuse reflectance absorption spectrum of In2O3 and INTG; c is the bandgap width of In2O3 and INTG; d is the valence band X-ray photoelectron spectrum (vb-XPS) of INTG; e is the electron paramagnetic resonance spectrum of hydroxyl radicals captured by the capture agent DMPO; f is the electron paramagnetic resonance spectrum of singlet oxygen captured by the capture agent TMPO; g is the mechanism diagram of the photodynamic generation of reactive oxygen by the In2O3-Ti3C2@GOx biological heterojunction.

[0049] Figure 3 The physicochemical characterization of the In2O3-Ti3C2@GOx hydrogel microneedle (GITG) prepared by the present invention. Among them, a is the needle tip photo and scanning electron microscope picture of GM and GITG microneedles; b is the GITG puncture experiment skin experiment; c is the water contact angle experiment; d is the quantitative result of the water contact angle experiment; e is the pressure test curve of the microneedle, and f is the Young's modulus of the microneedle.

[0050] Figure 4 Characterization of the photothermal performance of GITG microneedles. Among them, a is the photothermal temperature rise image of GM, GIO, GTC, and GITG; b is the thermal imaging image of the wound surface of rats treated with GM and GITG microneedles; c is the photothermal temperature rise curve of GM, GIO, GTC, and GITG; d is the temperature rise curve of GITG with different power illumination; e is the photothermal cycle curve of GITG microneedles.

[0051] Figure 5The chemical dynamics and photodynamics test characterization of GITG microneedles. Among them, a is the TMB color development experiment when H2O2 is used as a substrate; b is the TMB color development experiment when glucose is used as a substrate; c is the MB fading experiment when H2O2 is used as a substrate; d is the MB fading experiment when glucose is used as a substrate; e is the DTNB fading experiment when H2O2 is used as a substrate; f is the DTNB fading experiment when glucose is used as a substrate; g is the DPBF fading experiment of different materials (GM, GIO, GTC, GIT, GITG) under NIR light irradiation; h is the DPBF fading experiment over time without adding any material under NIR light irradiation.

[0052] Figure 6 The antibacterial performance test of GITG microneedles. Among them, a is the Staphylococcus aureus proliferation experiment, b is the Escherichia coli proliferation experiment; c is the Staphylococcus aureus and Escherichia coli cloning experiment; d is the antibacterial rate obtained from the Escherichia coli cloning experiment; e is the antibacterial rate obtained from the Staphylococcus aureus cloning experiment.

[0053] Figure 7 The wound healing results of GITG. Among them, a is the wound healing photos on the 4th, 7th, 10th and 14th days; b is the pathological staining results of the wound on the 4th, 7th and 14th days; c, d, e and f are the statistical results of the wound healing rate on the 4th, 7th, 10th and 14th days respectively. DETAILED DESCRIPTION

[0054] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0055] The present invention provides a synthesis scheme of In2O3-Ti3C2@GOx bioheterojunction. In2O3-Ti3C2 is prepared by hydrothermal method and high temperature calcination method. The details are as follows:

[0056] Synthesis of Ti3C2: ① Prepare a 50 mL polytetrafluoroethylene hydrothermal reactor, 10 mL of 50% hydrofluoric acid, 10 mL of 12 mol / L hydrochloric acid, 5 mL of deionized water and 1 g of titanium aluminum carbide (Ti3AlC2). ② Add hydrofluoric acid, concentrated hydrochloric acid and deionized water to the reactor respectively, mix well and place on a magnetic stirrer for stirring. When the temperature rises to 35°C, add titanium aluminum carbide (Ti3AlC2) and continue stirring for 12 h. ③ Centrifuge after 12 h (3500 r / min × 1 min), pour off the supernatant, and wash the remaining black precipitate repeatedly with deionized water and centrifuge until Ph is neutral. ④ Weigh 1 g of LiCl and add it to 20 mL of deionized water for ultrasonic dissolution. Pour the solution into the above-obtained precipitate, mix well, and continue stirring with a magnetic stirrer for 12 h. ⑤ Centrifuge the above solution (3500 r / min × 1 min), remove the supernatant, add deionized water and centrifuge (5000 r / min × 1min), pour the obtained black liquid into a beaker after centrifugation, ultrasonicate for 15 min, and finally dry to obtain a single layer of Ti3C2.

[0057] Synthesis of In2O3-Ti3C2: ① Weigh 100 mg of In(NO3)3·xH2O and 100 mg of Ti3C2, then add 30 mL of anhydrous ethanol and 7 mL of ammonia water (25wt%) and mix well. ② Transfer the mixed solution to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, react at 120°C for 24 h, centrifuge to obtain a precipitate, and wash it three times with deionized water. ③ After washing, place the precipitate in a 60°C drying oven and dry it for 10 h. ④ The obtained dry precipitate was calcined in a muffle furnace at 500°C for 2 h under oxygen isolation to obtain In2O3-Ti3C2. Among them, x in In(NO3)3·xH2O is 1~10.

[0058] Synthesis of In2O3-Ti3C2@GOx: 10 mg of In2O3-Ti3C2 nanomaterials were weighed, soaked in 100 μL of GOx (2 mg / mL) solution, incubated at -4 °C overnight, and freeze-dried.

[0059] In order to compare the improvement efficiency of the photodynamic effect of In2O3-Ti3C2@GOx with that of In2O3 and Ti3C2, In2O3 was synthesized by the following method.

[0060] Synthesis of In2O3: ① Weigh 200 mg of In(NO3)3·xH2O, then add 30 mL of anhydrous ethanol and 7 mL of ammonia water (25wt%) and mix well. ② Transfer the mixed solution to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, react at 120°C for 24 h, centrifuge to obtain a white precipitate, and wash it three times with deionized water. ③ After washing the precipitate, dry it in a 60°C drying oven for 10 h to obtain In(OH)3. ④ Calcinate In(OH)3 in a muffle furnace at 500°C for 2 h to obtain In2O3. Wherein, x in In(NO3)3·xH2O is 1~10.

[0061] Then, the present invention observed the morphology and structure of the above-mentioned material by scanning electron microscopy, and performed elemental analysis on In2O3-Ti3C2@GOx by energy spectrum analysis technology; then, X-ray diffraction (XRD) experiment and X-ray photoelectron spectroscopy (XPS) experiment were used to analyze the crystal structure and elemental composition of In2O3-Ti3C2@GOx; finally, Fourier transform infrared spectroscopy (FT-IR) was used to prove that the material was successfully loaded with glucose oxidase.

[0062] Transmission electron microscopy was used to observe the heterojunction structure of In2O3-Ti3C2@GOx, and its lattice spacing and lattice constant were analyzed. UV-Vis diffuse reflectance spectroscopy (UV-Vis) was used to analyze In2O3-Ti3C2@GOx, In2O3 and Ti3C2, and their respective bandgap widths were calculated. The positions of their respective valence bands were analyzed by vb (valence band)-XPS, and the complete band gap structure of In2O3-Ti3C2@GOx was obtained. Then, electron paramagnetic resonance (EPR) experiments were used to detect the ability of In2O3-Ti3C2@GOx to produce active oxygen in the presence of hydrogen peroxide.

[0063] Compared with In2O3, In2O3-Ti3C2@GOx has enhanced absorption in the near-infrared region. The band gap of In2O3 is 2.82 eV, and the band gap of In2O3-Ti3C2@GOx is 2.50 eV, which is significantly reduced. At the same time, vb-XPS valence band spectrum analysis was used to determine that the valence band position of In2O3-Ti3C2@GOx is at 2.12 eV, while H2O2 / ·OH, H2O2 / O2 and O2 / 1 The standard electromotive force of O2 is +0.32 eV, +0.684 and +1.78 eV, indicating that theoretically the energy of the photoelectrons generated by In2O3-Ti3C2@GOx is sufficient for the above reactions to occur, and the photodynamic force can produce a large amount of ·OH and 1 O2.

[0064] In addition, the present invention also provides a preparation technology solution and application of In2O3-Ti3C2@GOx loaded bioheterojunction hydrogel microneedle (GITG).

[0065] The hydrogel microneedles use methacrylic anhydride gelatin (GelMA) as the base material, and the specific synthesis method is as follows:

[0066] Preparation of methacrylated gelatin (GelMA): 80 g of gelatin was added to 720 g of deionized water and stirred in a 50°C water bath to fully dissolve it. Subsequently, 40 g of methacrylic anhydride solution was added to the solution and stirring was continued overnight. After stirring, the solution was placed in a 3500 molecular weight dialysis bag and dialyzed with distilled water for 72 h. The precipitate was then removed by centrifugation (3000 r / min × 5 min). The centrifuged methacrylated gelatin solution was evenly poured into a culture dish and freeze-dried to obtain methacrylic anhydride gelatin.

[0067] Preparation of In2O3-Ti3C2@GOx bioheterojunction hydrogel microneedles: 2-5 mg / mL of In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion and 2-5 wt‰ of photoinitiator 2959 were added to a beaker and stirred evenly at 37 °C to obtain In2O3-Ti3C2@GOx gel suspension. In2O3-Ti3C2@GOx gel suspension was poured into a microneedle mold (15 × 15 microneedle array, needle height 500 µm, needle distance 700 µm, substrate diameter 270 µm) and placed in a vacuum drying oven, then vacuumed to remove bubbles so that the In2O3-Ti3C2@GOx gel suspension filled the needle tip, and the base solution was added after the bubbles were sucked and scraped with a pipette, and then the base solution was added and exposed to light, and finally dried and demolded to obtain In2O3-Ti3C2@GOx composite microneedles. The base solution is prepared from 15-25wt% methacrylic anhydride gelatin aqueous solution and 2-5wt‰ of photoinitiator 2959 added to the dispersion.

[0068] Scanning electron microscopy, pressure test, water contact angle test, skin puncture test, etc. were used to test the physical and chemical properties of the four microneedles, and the water absorption and punctureability of the microneedles were tested. 2 The microneedles were irradiated with 808 nm near-infrared light (NIR), and the temperature change images were recorded with a thermal imager. 3,3',5,5'-tetramethylbenzidine (TMB), methyl blue (MB), 1,3-diphenylisobenzofuran (DPBF), and 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) were used to detect the photodynamic activity of the four microneedles under near-infrared light irradiation, and the ability of the microneedles to produce reactive oxygen species was detected.

[0069] Single colonies of Staphylococcus aureus and Escherichia coli were cultured in an incubator for 3 h, and plate cloning experiments and bacterial proliferation experiments were performed after amplification to detect the antibacterial properties of the above-mentioned microneedles.

[0070] Streptozotocin was used to establish a diabetic rat model. After the model was successfully established, a 1.5 × 1.5 cm 2 The wound was covered with 200 μl (OD600 was 0.3-0.6) of Staphylococcus aureus solution. The rats were divided into 5 groups, namely, blank, gauze, 3M commercial, GITG, and GITG / N groups, and given corresponding treatment measures. The wound repair was observed on days 0, 4, 7, and 14, and the tissues were collected for hematoxylin and eosin (HE) staining to evaluate the application potential of In2O3-Ti3C2@GOx bioheterojunction hydrogel microneedles.

[0071] The present invention is further described in conjunction with specific examples. The following examples are only for explaining the present invention and are not intended to limit the content thereof. If the specific experimental conditions are not specified in the examples, they are usually carried out under conventional conditions or under conditions recommended by the sales company; the materials and reagents used in the examples, unless otherwise specified, can be purchased through commercial channels.

[0072] Example 1

[0073] Example 1 is the synthesis method and performance characterization of In2O3-Ti3C2@GOx (INTG) bioheterojunction.

[0074] (1) Synthesis of Ti3C2:

[0075] ① Prepare a 50 mL polytetrafluoroethylene hydrothermal reactor, 10 mL of 50 wt% hydrofluoric acid, 10 mL of 12 mol / L hydrochloric acid, 5 mL of deionized water, and 1 g of titanium aluminum carbide (Ti3AlC2).

[0076] ② Add hydrofluoric acid, concentrated hydrochloric acid and deionized water to the reactor respectively, mix well and stir on a magnetic stirrer. When the temperature rises to 35 °C, add titanium aluminum carbide (Ti3AlC2) and continue stirring for 12 h.

[0077] ③ Centrifuge after 12 h (3500 r / min × 1 min), pour off the supernatant, and wash the remaining black precipitate repeatedly with deionized water and centrifuge until the pH is neutral.

[0078] ④ Weigh 1 g of lithium chloride and add it to 20 mL of deionized water for ultrasonic dissolution. Pour the solution into the above-obtained precipitate, mix thoroughly, and continue stirring with a magnetic stirrer at room temperature for 12 h.

[0079] ⑤ Centrifuge the above solution (3500r / min × 1 min), remove the supernatant, add deionized water and centrifuge (5000r / min × 1 min), pour the obtained black liquid into a beaker after centrifugation, ultrasonicate for 15 min, and finally dry to obtain a single layer of Ti3C2.

[0080] (2) Synthesis of In2O3-Ti3C2:

[0081] ① Weigh 100 mg of In(NO3)3·xH2O (x is 1) and 100 mg of Ti3C2, then add 30 mL of anhydrous ethanol and 7 ml of ammonia water (25wt%) and mix well.

[0082] ② The mixed solution was transferred to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, reacted at 120 °C for 24 h, and then centrifuged to obtain a precipitate, which was then washed three times with deionized water.

[0083] ③ After washing, the precipitate was placed in a 60 ℃ drying oven and dried for 10 h.

[0084] ④ The obtained dry precipitate was calcined in a muffle furnace at 500 °C for 2 h under oxygen-free conditions to obtain In2O3-Ti3C2.

[0085] (3) Synthesis of In2O3-Ti3C2@GOx:

[0086] 10 mg of In2O3-Ti3C2 nanomaterials were weighed, soaked in 100 μl of GOx (2 mg / ml) solution, incubated at -4 °C overnight, and freeze-dried to obtain In2O3-Ti3C2@GOx.

[0087] In order to compare the improvement efficiency of the photodynamic effect of In2O3-Ti3C2@GOx with that of In2O3 and Ti3C2, In2O3 was synthesized by the following method.

[0088] Synthesis of In2O3: ① Weigh 200 mg of In(NO3)3·H2O, then add 30 mL of anhydrous ethanol and 7 mL of ammonia water (25wt%) and mix well. ② Transfer the mixture to a 50 mL stainless steel reactor lined with polytetrafluoroethylene, react at 120°C for 24 h, centrifuge to obtain a white precipitate, and wash it three times with deionized water. ③ After washing the precipitate, dry it in a 60°C drying oven for 10 h to obtain In(OH)3. ④ Calcinate In(OH)3 in a 500°C muffle furnace for 2 h to obtain In2O3.

[0089] Test results and analysis:

[0090] Figure 1The scanning electron microscope morphologies of Ti3AlC2, Ti3C2, In2O3, In2O3-Ti3C2, and In2O3-Ti3C2@GOx are shown in a. Figure 1 In2O3-Ti3C2 is named INTG and In2O3-Ti3C2 is named INT. Figure 1 As can be seen from a in the figure, In2O3 is in the shape of nanospheres and Ti3C2 is in the shape of a single-layer two-dimensional planar structure. In the In2O3-Ti3C2@GOx composite material, In2O3 and GOx are successfully loaded on the surface of Ti3C2.

[0091] Figure 1 b is an XRD test, which shows that the In2O3-Ti3C2@GOx composite material has the characteristic peaks of Ti3C2 and In2O3, but does not contain the characteristic peak of Al; Figure 1 c in the figure is the XPS test, which shows that In2O3-Ti3C2@GOx has characteristic peaks of each component; Figure 1 The d in the figure is the semi-quantitative result of In2O3-Ti3C2@GOx scanning electron microscope energy spectrum analysis (EDS). Figure 1 Figure f is the scanning electron microscope energy spectrum analysis (EDS) image of In2O3-Ti3C2@GOx. The appearance of N element preliminarily indicates that glucose oxidase is successfully loaded on the In2O3-Ti3C2@GOx composite material. Figure 1 e in is the Fourier transform infrared spectrum of the In2O3-Ti3C2@GOx composite material, and the figure indicates that INTG has -CH2, C=O, and C=N functional groups.

[0092] The above results indicate that In2O3-Ti3C2@GOx (INTG) was successfully prepared.

[0093] Figure 2 Figure a is the transmission electron microscopy result of INTG, showing its heterojunction structure. Ti3C2 and In2O3 form a heterojunction at the interface and produce a staggered lattice. Figure 2 Figure b shows the UV-visible diffuse reflectance absorption spectra of INTG and In2O3. After forming a heterojunction with Ti3C2, the absorption of INTG at 300-900 nm is significantly enhanced; Figure 2 c in the figure is the band gap of INTG and In2O3. The calculated band gap of INTG is 2.50 eV, which is narrower than 2.82 eV of In2O3. Figure 2 The d in the figure is the vb-XPS of INTG. The calculated valence band position of INTG is +2.12 eV. Figure 2 The e in the equation is the result of the electron paramagnetic resonance spectrum of hydroxyl radicals captured by the capture agent DMPO. Figure 2f in the figure is the result of the electron paramagnetic resonance spectrum of the capture agent TMPO capturing singlet oxygen, which shows that in the presence of H2O2, the capture agent can capture hydroxyl radicals and singlet oxygen, and near-infrared light can enhance this effect; Figure 2 Figure g shows the mechanism diagram of photodynamic production of reactive oxygen species by INTG heterojunction.

[0094] Example 2

[0095] Example 2 is a synthesis method, performance characterization and application evaluation of a bioheterojunction hydrogel microneedle (GITG) loaded with In2O3-Ti3C2@GOx.

[0096] (1) Preparation of methacryloyl gelatin (GelMA): 80 g of gelatin was added to 720 g of deionized water and stirred in a 50°C water bath to fully dissolve it. Subsequently, 40 g of 94 wt% methacrylic anhydride solution was added to the solution and stirred overnight. After stirring, the solution was placed in a 3500 molecular weight dialysis bag and dialyzed with distilled water for 72 h. The solution was then centrifuged to remove the precipitate (3000 r / min × 5 min). The centrifuged methacrylic anhydride gelatin solution was evenly poured into a culture dish and freeze-dried to obtain methacrylic anhydride gelatin.

[0097] (2) Preparation of In2O3-Ti3C2@GOx methacrylic gelatin sample dispersion: First, 5 g of methacrylic gelatin was added to 20 g of deionized water and stirred at 70 °C until the methacrylic gelatin was completely dissolved to obtain a 20 wt% methacrylic gelatin aqueous solution. Then, 2 mg of In2O3-Ti3C2@GOx bioheterojunction was added to 1 mL of methacrylic anhydride gelatin aqueous solution and mixed evenly to obtain a 2 mg / ml In2O3-Ti3C2@GOx methacrylic gelatin sample dispersion.

[0098] (3) Preparation of In2O3-Ti3C2@GOx composite microneedles: 2 mg / mL of In2O3-Ti3C2@GOx methacryloyl gelatin sample dispersion and 5 wt‰ of photoinitiator 2959 were added into a beaker and stirred evenly at 37 °C to obtain In2O3-Ti3C2@GOx gel suspension.

[0099] In2O3-Ti3C2@GOx gel suspension was poured into a microneedle mold (15 × 15 microneedle array, needle height 500 µm, needle distance 700 µm, substrate diameter 270 µm) and placed in a vacuum drying oven. Vacuum was then used to remove bubbles so that the In2O3-Ti3C2@GOx gel suspension filled the needle tip. After a pipette was used to suck and scrape out bubbles, the substrate solution was added and exposed to light. Finally, the mold was dried and demolded to obtain the In2O3-Ti3C2@GOx composite microneedle, named GITG.

[0100] Similarly, blank (pure methacrylated gelatin) microneedles, Ti3C2 microneedles, In2O3 microneedles and In2O3-Ti3C2 microneedles were prepared according to the method of Example 2 and named GM, GTC, GIO and GIT, respectively; the 808 nm near-infrared light treatment group was marked as / N, that is, the 808 nm near-infrared light treatment group of GITG was marked as GITG / N.

[0101] Test results and analysis:

[0102] GM microneedles and GITG microneedles were observed using optical microscopy and scanning electron microscopy, and it can be seen that In2O3-Ti3C2@GOx is distributed all over the GITG microneedles ( Figure 3 a); GITG microneedles were used to puncture the skin of nude mice. The results showed that the microneedles can effectively puncture the skin. See the photo results. Figure 3 b in; Figure 3 c and Figure 3 Figure d in the figure is the water contact angle experiment and its results. It can be seen that the introduction of Ti3C2, In2O3, and In2O3-Ti3C2@GOx did not change the hydrophilicity of GelMA hydrogel microneedles; Figure 3 The e in the figure is the result of the microneedle pressure test of each group. Figure 3 f is the Young's modulus of the microneedles in each group, which are 139.77 ± 4.15 KPa for the GM group, 90.63 ± 5.65 KPa for the GIO group, 109.71 ± 1.97 KPa for the GTC group, and 118.74 ± 2.26 KPa for the GITG group. The introduction of nanoparticle components reduced the mechanical strength of the microneedles, but the composite structure of the GITG group and the presence of high-molecular glucose oxidase did not significantly affect the mechanical strength of the microneedles.

[0103] Figure 4 a in the figure is the microneedle at 0.12 W / cm 2 The thermal imaging results under 808 nm light showed that the GTC and GM groups had no obvious stable changes under 808 nm light, and the GTC group had the best heating effect. The GITG group reached 45°C for low-temperature photothermal therapy after 60 s of light exposure due to the modification of Ti3C2. Figure 4b is the thermal imaging image of GM and GITG microneedles used for wound treatment in rats; Figure 4 c in the figure is the photothermal heating curve results of different microneedles; Figure 4 Figure d is the temperature rise curve of GITG microneedle under different powers (0.03W, 0.04W, 0.12W, 0.21W, 0.31W) of light. As the irradiation light power increases, the maximum temperature reached by the microneedle also increases; Figure 4 The figure e in the figure represents the photothermal cycle stability experiment of GITG microneedles. The results show that the photothermal heating properties of GITG have not changed under multiple cycles of illumination and no illumination, and the stability is good.

[0104] Figure 5 a in the figure is the experiment of measuring hydroxyl free radicals by TMB method under the condition of H2O2 as substrate. The results of TMB showed that the absorbance of GIT and GITG groups at 650 nm increased significantly, and this effect was enhanced under light irradiation. Figure 5 b in the figure is the TMB method for determining hydroxyl radicals under the condition of glucose as substrate. The results show that only the GITG group has a significant increase in absorbance at 650 nm, which oxidizes TMB. At the same time, GITG / N produces more hydroxyl radicals. Figure 5 The experimental results of a and b in the figure show that when H2O2 or glucose is used as substrate, GITG can produce hydroxyl radicals under NIR light irradiation; Figure 5 When c is H2O2 as substrate, the ability of each group of microneedles to generate hydroxyl free radicals was determined by the methylene blue (MB) method. Figure 5 The ability of each group of microneedles to generate hydroxyl free radicals was also determined using the methylene blue (MB) method when d-glucose in the solution was used as the substrate. Figure 5 The experimental results of c and d in Figure 3 show that when H2O2 or glucose is used as a substrate, GITG can produce hydroxyl radicals under NIR light irradiation, which is consistent with the results of TMB experiments; Figure 5 When e is H2O2 as substrate, DTNB is used to detect the glutathione oxidase activity (GPX) of the microneedle. Figure 5 The "e" in the figure indicates that GIO has intrinsic GPX enzyme activity, and GITG has stronger GPX enzyme activity than GIO. At the same time, GITG has stronger GPX enzyme activity under light drive, which can effectively consume glutathione (GSSH) in bacteria and enhance the killing effect of reactive oxygen on bacteria. Figure 5 When f is glucose as substrate, the DTNB method is used to detect the glutathione oxidase activity (GPX) of the microneedle. Figure 5 Figure f proves that GITG can effectively oxidize GSSH in the presence of glucose, and this property is more suitable for diabetic wounds; therefore, according to Figure 5The experimental results of Figures e and f show that when H2O2 or glucose is used as a substrate, GITG has glutathione oxidase activity (GPX) and can oxidize GSH to GSSG. GITG is light-responsive and can enhance GPX activity. Figure 5 g in the figure is the DPBF fading experiment of different materials (GM, GIO, GTC, GIT, GITG) under NIR light irradiation. Figure 5 h in the figure is the fading experiment of DPBF over time when no material is added under NIR light. Figure 5 g and h in the figure were detected by DPBF method under light conditions. 1 O2's capabilities Figure 5 g and Figure 5 The results in Figure 3 show that under light-driven conditions, GIT and GITG can produce 1 O2 oxidizes DPBF and causes the solution to fade, resulting in a decrease in absorbance at 420 nm.

[0105] Blank (GM), ampicillin (Amp), GIO, GTC, GITG, GITG / N (N represents 808 nm near-infrared light treatment for 30 min) were mixed evenly with 1 mL of Staphylococcus aureus and Escherichia coli with an OD600 of 0.3-0.6, and then added to 10 mL of culture medium for 3 h. This step was used as pretreatment. (1) Then 200 μL of the bacterial solution was taken out and its absorbance at 600 nm was measured using an ELISA reader. Then it was returned to the incubator for routine culture and continuously measured for 4 h to obtain the bacterial proliferation curve, where Figure 6 a in the experiment is the proliferation of Staphylococcus aureus (in Figure 6 aureus in a), Figure 6 b is an experiment on the proliferation of E. coli, which shows that GITG significantly inhibits the proliferation of Staphylococcus aureus and E. coli. The inhibitory effect of GITG / N is even stronger than that of GITG, indicating that NIR light can promote the antibacterial effect of GITG. (2) Take out 100 μL of the bacterial solution and dilute it by 10 8 After the multiple was calculated, 50 μL was evenly inoculated on LB solid medium, spread evenly with a triangular spreading rod, and the culture dish was inverted in a 37 ℃ incubator for overnight incubation. Then the culture dish was taken out to observe the colony formation and take photos of the bacterial clones. Figure 6 The c in the figure is the result of the Staphylococcus aureus and Escherichia coli cloning experiment, and the antibacterial rate is calculated. Figure 6 The d in the equation is the inhibition rate obtained from the E. coli cloning experiment. Figure 6The "e" in the figure is the inhibition rate obtained from the Staphylococcus aureus cloning experiment. The results showed that the inhibition rates of the GITG microneedle photothermal therapy group against Staphylococcus aureus and Escherichia coli were 95.19 ± 2.78% and 96.95 ± 2.69%, respectively, with no significant statistical difference compared with the positive control group Amp.

[0106] The application effect of GITG microneedles was evaluated using the diabetic rat infectious wound model. Specifically, 100-150 g SD rats were purchased and fed with high sugar and high fat for 4-6 weeks. Blood sugar was monitored daily. When blood sugar was greater than 11.1 mM and body weight reached 250 g, high sugar and high fat feeding was stopped. The rats were randomly divided into five groups: blank group (untreated group), gauze group (treated with gauze), 3M commercial dressing group, GITG group, and GITG / N group. After anesthetizing the rats, the hair was shaved and a punch was used to make a wound model. The wound area was 1.5 × 1.5 cm 2 , and then injected with 200 μL of Staphylococcus aureus with OD600 between 0.3 and 0.6. Each group was given the corresponding treatment method. The GITG experimental group was given 808 nm near-infrared light treatment for 15 minutes every day for the first 4 days. The wound healing of the rats was observed and photographed every day. The surgery day was designated as day 0, and photographs were taken on the 4th, 7th, 10th, and 14th days after surgery ( Figure 7 a in the figure), statistical wound healing rate ( Figure 7 c, d, e and f in the figure), and the wound surface was surgically cut and stained with HE ( Figure 7 b). On the 4th day, the healing rate of the GITG / N group was 50.7 ± 2.16%, which was better than the 36.1 ± 3.48% of the GITG group, indicating that the synergistic treatment of photothermal and photodynamic therapy effectively treated the infection. At the same time, both groups were significantly better than the 22.22 ± 3.16% of the blank group; similar results were obtained on the 7th and 10th days. On the 14th day, the healing rate of the GITG / N group was 97 ± 2.18%, and most of the wounds had healed. HE pathological staining also showed that the wounds had healed, with new skin squamous epithelium covering and collagen deposition; the GITG group was 92.9 ± 2.60%, the 3M group was 91 ± 2.83%, and the gauze group was 82.85 ± 3.67%, while the blank group wound healing rate was only 73.72 ± 3.56%.

[0107] In summary, the above test results show that the GITG microneedles prepared in Example 2 have good hydrophilicity, mechanical strength and stability, can effectively oxidize glutathione, inhibit the proliferation of Staphylococcus aureus and Escherichia coli, and have a good therapeutic effect on infectious wounds in diabetic rats.

[0108] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an In2O3-Ti3C2@GOx bioheterojunction, characterized in that: The following steps are involved: S1. Add In(NO3)3·xH2O and Ti3C2 to a solvent and mix well to obtain a mixed solution; heat the mixed solution, and centrifuge to obtain a precipitate after the reaction is completed; wash and dry the precipitate, and then calcine it under oxygen-free conditions to obtain In2O3-Ti3C2; wherein x in In(NO3)3·xH2O is 1 to 10; S2. Soaking the In2O3-Ti3C2 in a glucose oxidase solution and freeze-drying the solution to obtain an In2O3-Ti3C2@GOx bioheterojunction.

2. The preparation method according to claim 1, characterized in that: The preparation method of Ti3C2 comprises the following steps: Add hydrofluoric acid, concentrated hydrochloric acid and deionized water to the reaction container and mix well; heat the reaction container, and when the heating temperature rises to 30°C to 40°C, add titanium aluminum carbide to the reaction container, continue stirring for 8h to 16h, centrifuge to obtain a black precipitate, and wash until the pH is neutral; Adding LiCl into deionized water and dissolving it to obtain a LiCl solution; The LiCl solution and the black precipitate are mixed and stirred for 8 h to 16 h, the obtained solution is centrifuged to remove the supernatant, deionized water is added and centrifuged again, the obtained black liquid is subjected to ultrasonic treatment, and finally dried to obtain a single layer of Ti3C2; The ratio of the added amounts of hydrofluoric acid, concentrated hydrochloric acid, titanium aluminum carbide and LiCl is 8 mL to 12 mL: 8 mL to 12 mL: 0.8 g to 1.2 g: 0.8 g to 1.2 g; The concentration of the hydrofluoric acid is 45wt%~55wt%; The concentration of the hydrochloric acid is 10 mol / L~14 mol / L.

3. The preparation method according to claim 1, characterized in that: In step S1, The heating temperature is 100℃~140℃, and the heating time is 20h~28h; The drying temperature is 50℃~70℃, and the drying time is 8h~12h; The calcination temperature is 480℃~520℃, and the calcination time is 1.5h~2.5h; The solvent includes anhydrous ethanol and aqueous ammonia with a concentration of 20wt% to 30wt%; The ratio of the added amounts of In(NO3)3·xH2O, Ti3C2, anhydrous ethanol and aqueous ammonia is 80mg~120mg:80mg~120mg:25mL~35mL:6mL~8mL.

4. The preparation method according to claim 1, characterized in that: In step S2, The concentration of the glucose oxidase solution is 1.5 mg / mL to 2.5 mg / mL; The ratio of the added amount of In2O3-Ti3C2 to the glucose oxidase solution is 8mg~12mg:80μL~120μL; The soaking temperature is -5℃~-3℃, and the soaking time is 10h~14h.

5. An In2O3-Ti3C2@GOx bioheterojunction, characterized in that: The method is prepared by any one of claims 1 to 4.

6. A hydrogel microneedle loaded with the In2O3-Ti3C2@GOx bioheterojunction according to claim 5, characterized in that: The preparation raw materials include: methacrylic anhydride gelatin, In2O3-Ti3C2@GOx biological heterojunction and photoinitiator.

7. A method for preparing a hydrogel microneedle as claimed in claim 6, characterized in that: The following steps are involved: Mixing methacrylic anhydride gelatin with deionized water and heating to obtain a 15 wt % to 25 wt % methacrylic anhydride gelatin aqueous solution; The methacrylic anhydride gelatin aqueous solution is mixed with the In2O3-Ti3C2@GOx bioheterojunction to obtain an In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion; The In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion is evenly mixed with a photoinitiator to obtain an In2O3-Ti3C2@GOx gel suspension; The In2O3-Ti3C2@GOx gel suspension is poured into the microneedle mold, dried, and bubbles are removed to fill the needle tip with the In2O3-Ti3C2@GOx gel suspension. After adding the substrate solution, the mold is exposed to light and demolded to obtain the In2O3-Ti3C2@GOx composite microneedle.

8. The preparation method according to claim 7, characterized in that: The preparation method of the methacrylic anhydride gelatin comprises: Add gelatin to deionized water, heat to 45°C-50°C and stir to fully dissolve it, then add methacrylic anhydride solution to the solution, continue stirring, put the solution into a dialysis bag after stirring, dialyze with distilled water for 68 h-76 h, then centrifuge to remove the precipitate, and evenly freeze-dry the centrifuged methacrylated gelatin solution to obtain methacrylated gelatin; Wherein, the mass ratio of the gelatin, methacrylic anhydride solution and deionized water is 1-3:0.5-1.5:16-20.

9. The preparation method according to claim 7, characterized in that: The concentration of the In2O3-Ti3C2@GOx methacrylated gelatin sample dispersion is 2 mg / mL to 5 mg / mL; The base solution is prepared from a 15-25wt% methacrylic anhydride gelatin aqueous solution and a photoinitiator, wherein the amount of the photoinitiator added is 2wt‰~5wt‰ of the In2O3-Ti3C2@GOx methacrylic anhydride gelatin sample dispersion; The preparation method of the In2O3-Ti3C2@GOx gel suspension specifically includes: The In2O3-Ti3C2@GOx methacryloyl gelatin sample dispersion and the photoinitiator are added into a container, and stirred evenly at 35°C~39°C to obtain the In2O3-Ti3C2@GOx gel suspension, wherein the amount of the photoinitiator added is 2wt‰~5wt‰ of the amount of the In2O3-Ti3C2@GOx methacryloyl gelatin sample dispersion added.

10. Use of the hydrogel microneedle according to claim 6 or the hydrogel microneedle prepared by the method according to any one of claims 7 to 9 in preparing a product for treating diabetic wounds.

Citation Information

Patent Citations

  • Photo-thermal treatment composition containing glucose oxidase as well as medical instrument and application of photo-thermal treatment composition

    CN116966277A

  • Glucose-responsive antibacterial nano-composite microneedle patch as well as preparation method and application thereof

    CN117643568A